Implications of Planting a Living Pharmacy on the Economy of Sumberagung Weleri District Kendal Regency - Laili Hidayatun Nikmah; Wahyu Ningrum Sulistyowati; Tissa Aunilla; Adellia Putriani; Selly Novita Sari; Nida Naswa; Ahmad Faqih (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Indonesia is one of the countries that cultivate various plants. Plants are not only used for food or decoration, plants are also very useful as medicines and healers. Plants that can be used to treat and cure diseases are commonly called live pharmacies. live pharmacy plants are quite useful to be used as a source of business because they can be sold and certainly improve the village economy.This research method uses a practical approach directly by going to the community to conduct counseling and planting practices. The results of this study are that the community is still unfamiliar with the concept of live pharmacy, with the practice of planting and counseling about live pharmacy making the Sumber Agung Village Community who are present there become more aware of the use of vacant land to plant useful plants.